2001
DOI: 10.1136/heart.85.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Bayesian index for predicting major adverse cardiac events with percutaneous transluminal coronary angioplasty

Abstract: Objective-To create a risk model for predicting major adverse complicating events of percutaneous transluminal coronary angioplasty (PTCA), and to test the accuracy of the model on a prospective cohort of patients Setting-Tertiary cardiac centre Methods-Available software can predict probabilities of events using Bayes's theorem. To establish the accuracy of these predictive tools, a Bayes table was created to evaluate major adverse complicating events (MACE)-death, emergency coronary artery bypass grafting (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…24 This model uses Bayes theorem and was developed on 1500 consecutive patients who underwent PCI starting from January 1995. The variables identified as predictive of MACE were cardiogenic shock, ejection fraction , 30%, Figure 1 Receiver operator characteristic (ROC) curve for multivariate prediction model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 This model uses Bayes theorem and was developed on 1500 consecutive patients who underwent PCI starting from January 1995. The variables identified as predictive of MACE were cardiogenic shock, ejection fraction , 30%, Figure 1 Receiver operator characteristic (ROC) curve for multivariate prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being developed on a cohort of patients from the mid 1990s, de Belder's model is limited by the Bayesian assumption that all risk factors are independent and therefore would have a tendency to overestimate the risk. 24 Strengths and meaning of the NWQIP model…”
Section: Discussionmentioning
confidence: 99%
“…There are, in fact, more than half-a-dozen other scoring systems which have been developed for PCI, from the days of balloon angioplasty to the modern era of drug-eluting stents and glycoprotein IIb/IIIa inhibitors. [4][5][6][7][8][9][10][11][12] They have confirmed that the main risk factors are age, recent MI, shock, emergency case, poor left ventricular function, renal impairment, peripheral vascular disease, multi-vessel disease, left main PCI and American Heart Association type C lesion. These studies all have their shortcomings.…”
Section: Shortcomingsmentioning
confidence: 89%
“…Moreover, there is concern about their current applicability given the changes in practice that have taken place since the models were derived (eg, the use of thienopyridines, glycoprotein inhibitors and stents, as well as the greater application of PCI to patients with acute coronary syndromes). So far two models reported in the UK population setting have looked at major adverse cardiovascular and cerebrovascular events (MACCE) 17 18…”
mentioning
confidence: 99%